Overexpression of Populus transcription factor PtrTALE12 increases axillary shoot development by regulating WUSCHEL expression. (18th May 2020) - Bae, So-Young; Kim, Min-Ha; Cho, Jin-Seong; Park, Eung-Jun; Lee, Hyoshin; Kim, Jeong-Hoe; Ko, Jae-Heung
Abstract: The TALE (Three Amino acid Loop Extension) transcription factor family has been shown to control meristem formation and organogenesis in plants. To understand the functional roles of the TALE family in woody perennials, each of the TALE members of Populus trichocarpa was overexpressed in Arabidopsis as a proxy. Among them, the overexpression of PtrTALE12 (i.e., 35S::PtrTALE12) resulted in a dramatic increase of axillary shoot development with early flowering. Interestingly, expression of WUSCHEL ( WUS ), a central regulator of both apical and axillary meristem formation, was significantly increased in the 35S::PtrTALE12 Arabidopsis plants. Conversely, WUS expression was downregulated in 35S::PtrTALE12-SRDX (short transcriptional repressor domain) plants. Further analysis found that PtrTALE12, expressed preferentially in meristem tissues, directly regulates WUS expression in transient activation assays using Arabidopsis leaf protoplast. Yeast two-hybrid assays showed that PtrTALE12 interacts with SHOOT MERISTEMLESS (STM); however, the interaction does not affect the WUS expression. In addition, expression of both CIRCADIAN CLOCK ASSOCIATED1 ( CCA1 ) and LATE ELONGATED HYPOCOTYL ( LHY ) genes was suppressed accordingly for early flowering 35S::PtrTALE12 Arabidopsis. Indeed, transgenic poplars overexpressing PtrTALE12 as well as Arabidopsis plants overexpressing AtBLH11, a close homolog of PtrTALE12, phenocopied the 35S::PtrTALE12 Arabidopsis (i.e., increased axillary shoot development). Taken together, our results suggest that PtrTALE12 functions as a positive regulator of axillary shoot formation in both Arabidopsis and poplar.